The role of Ulama for developing Islamic civil society in the Bugis community of South Sulawesi: A historical perspective - Tajuddin, Muhammad Saleh; Mahmad, Muhamad Amar; Rofie, Mohamad Khadafi (2014)
This writing depicts the role of ulama in the Bugis community of South Sulawesi.The primary data will be source from interview with the Bugis intellectuals and other community figures who are working with the Bugis and Islamic civil society areas.Secondary documentary sources will be include books and journal articles on similar research topics, and conference papers. This approach analyzes the historical aspect of ulama role for developing of Islamic civil society in the Bugis community of South Sulawesi.In Analysing the role of ulama in South Sulawesi, I use Antony Gidden’s theory of structure (state) and agency to analyse the role ulama in South Sulawei, especially for improving of the Bugis civil society. The three Dato (Dato Di Tiro, Dato Sulaeman, and Dato Ri Bandang) and Syekh Yusuf were use structure (state) to develop Islamic civil society in the Bugis community, while K.H. Muhammad As’ad, K.H. Abdurrahman Ambo Dalle, and K.H.Ahmad Hasan Marzuki were use agency (pesantren and Islamic organization). In the 17th century, the ulama had a role in islamizing the Bugis community of South Sulawesi. According to historical notes, the Bugis embraced Islam between 1605 and 1611 when the prince of Bone Kingdom surrounded the Gowa Kingdom. Since that time, Islam became an important element of the Bugis culture. The three Dato, such as Dato Di Tiro, Dato Sulaeman, and Dato Ri Bandang had a role of Islamization in South Sulawesi as well as integrated local wisdoms, especially cultural and political aspects, with Islam. Syekh Yusuf had a role to develop Islamic civil society concept through state and cultural movement.In the 20th century, Islamic civil society was developed by the Bugis ulama (Islamic intellectuals), such as K.H. Muhammad As’ad, K.H. Abdurrahman Ambo Dalle, and K.H.Ahmad Hasan Marzuki through their agencies are called pesantren (Islamic boarding school) and organization.One interesting points of the situation in pesantren is that teaching proses uses the Bugis language as a proof they maintain the bugis values that has been integrated with Islam. In addition, K.H. Muhammad As’ad and K.H. Abdurrahman Ambo Dalle are moderate muslim intellectuals. It is different from K.H.Marzuki Hasan who is known as Islamic fundamentalist, although he was a student of K.H. Muhammad As’ad.